A problem with the recognition of penicillin-resistant pneumococci. Issue 11 (November 1980) - Rees, T; Waterworth, P M
Abstract : A strain of Streptococcus pneumoniae requiring 0.25 mg/1 penicillin to inhibit its growth was isolated from the antrum of a child who had no history of either foreign contacts or previous treatment with penicillin. The penicillin resistance was recognised by chance because the disc used contained substantially less than its stated content of 1.5 unit. When discs containing 2 units were used there was little reduction in size of the zone of inhibition.